Tariffs Tax the Poor More: Evidence from Household Consumption During the US-China Trade War - Hong Ma; Luca Macedoni; Jingxin Ning; Mingzhi (Jimmy) Xu (CESifo GmbH, 2025)
Using disaggregated US household expenditure data, we study the distributional consequences of the US-China trade war. We estimate a highly flexible demand system to compute household-specific price indexes. The increases in US tariffs on Chinese products between 2018 and 2019 led to an average price index increase of 1.09%, with a disproportionately larger impact on low-income households. Specifically, we document a 0.9 percentage point smaller increase in the household price index for the top 20% income households compared to the bottom 20%. The dif-ference stems from wealthier households' greater expenditure adjustments and smaller reductions in product variety.
Keywords: F14; D31; F13; 330; US-China trade war; tariffs; income inequality; distributional effects of tariffs; household consumption